TINJAUAN PENGETAHUAN MAHASISWA TENTANG PENULISAN ARTIKEL ILMIAH PADA E-JURNAL DI FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 801-808 , Ridwan (CIVED, 2015)
ABSTRACT Based on the Decree of DIKTI, to oblige to any universities in Indonesia in order to further improve the publication of scientific articles in e-journals. At Padang State University colleges, especially in the Faculty of Engineering, there are still many students who do not know about the e-journal and grammar write articles in e-journals and e-journals lack of use by students as a reference. This study aims to determine how much knowledge the students' writing a scientific article on the e-journal in FT UNP. This research was conducted on students who are in the writing of the year 2010 which registered incoming semester from January to June 2015 in the FT UNP. The number of samples in this study were 145 respondents. Data collection techniques using a questionnaire with Likert scale, data analysis using descriptive analysis. Results of this research, there are two indicators examined in this study and obtain results, ie indicators of knowledge that students need in writing a scientific article with the percentage 57.08%, including at high enough categories and indicators journal with the percentage 67.58% included in the category high. Keywords: Pengetahuan, Artikel